RISR‐N observations of the IMF By influence on reverse convection during extreme northward IMF. Issue 3 (22nd March 2017) - Maimaiti, M.; Ruohoniemi, J. M.; Baker, J. B. H.; Clauer, C. R.; Nicolls, Michael J.; Hairston, Marc R.
Abstract: Previous studies have demonstrated that the high‐latitude ionospheric convection is strongly influenced by the interplanetary magnetic field (IMF) direction. However, the temporal details of how the convection transitions from one state to another are still not understood completely. In this study, we analyze an interval on 12 September 2014 which provided a rare opportunity to examine dynamic variations in the dayside convection throat as the IMF transitioned from strong B y + to strong B z +. Between 18:00 and 20:00 UT the northward face of the Resolute Bay Incoherent Scatter Radar (RISR‐N) rotated through the noon sector and directly measured strengthening reverse convection flows in the dayside throat region that peaked at ∼2800 m/s. Near‐simultaneous measurements from DMSP satellites confirm the magnitude of the reverse convection and its proximity to the cusp. Time series comparison of the RISR‐N north‐south flows with the IMF B z component shows a remarkably high correlation, suggestive of strong linear coupling, with no sign of velocity saturation. Likewise, the east‐west flow variations were highly correlated with the changes in IMF B y . However, time‐lagged correlation analysis reveals that the IMF B y influence acted on a time scale 10 min shorter than that of the B z component. As a consequence, the manner in which the convection transitioned from the strong B y + condition to the strong B z + condition is inconsistent with either the antiparallel or component reconnection models. Instead, we suggest that these particular observations are consistent with two separate reconnection sites on the magnetopause driven independently by the IMF B y and B z components. Key Points: Direct RISR‐N measurements of onset of strong reverse convection flows in the dayside throat region Different timescales of the IMF Bz and By influences on flows in the dayside throat region Emergence of two separate reconnection sites on the magnetopause